PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER (NHT) BERBANTUAN ARTICULATE STORYLINE TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD DI GUGUS VII KECAMATAN BULELENG - Ni Kadek Intan Purwantari; I Nyoman Pancaria; I Gede Arya Wiradnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to investigate the effect of the Numbered Heads Together (NHT) learning model, supported by the Articulate Storyline based on Tri Hita Karana, on the science learning outcomes of fourth-grade elementary school children in Cluster VII, Buleleng District. The study sample consisted of an experimental class and a control class selected using cluster random sampling. A science learning outcome test was used to collect data, and a t-test was used for analysis. The results showed that students' science learning outcomes were significantly influenced by the learning paradigm (NHT), supported by the Articulate Storyline based on Tri Hita Karana. This model is suitable for implementation as a learning innovation in elementary school classes because it can increase student engagement, collaboration, and conceptual understanding.